2011
DOI: 10.1590/s0006-87052011005000003
|View full text |Cite
|
Sign up to set email alerts
|

Verificação da adaptabilidade e estabilidade de populações de cenoura pelos métodos AMMI, GGE biplot e REML/BLUP

Abstract: ResumoO objetivo desse estudo foi verificar a adaptabilidade e estabilidade de populações de cenoura diante de ambientes com cultivo orgânico e convencional e realizar a comparação entre as metodologias estatísticas utilizadas. O trabalho foi desenvolvido em 2007 e 2008, em cinco locais. Em São Gotardo (MG); Irecê (BA) e Gama (DF) foi realizado cultivo convencional e em PAD (DF) (Programa de Assentamento Dirigido do Distrito Federal) e Gama (DF) foi utilizado o sistema de cultivo orgânico. O delineamento exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 19 publications
(24 reference statements)
2
23
0
7
Order By: Relevance
“…This value was higher than that reported by Guerra et al (2009) and by Verissimo et al (2012), who applied AMMI analysis to sugarcane, and similar to results of Chavanne et al (2007) and Silva et al (2012), who used GGE Biplot analysis for sugarcane and carrots, respectively.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…This value was higher than that reported by Guerra et al (2009) and by Verissimo et al (2012), who applied AMMI analysis to sugarcane, and similar to results of Chavanne et al (2007) and Silva et al (2012), who used GGE Biplot analysis for sugarcane and carrots, respectively.…”
Section: Resultssupporting
confidence: 84%
“…Guerra et al (2009) and Verissimo et al (2012) identified genotypes and environments with same-sign PCI scores, with positive specific interactions for sugarcane. The classification of genotypes and environments established by Oliveira et al (2003) and Silva et al (2012) for soybean and carrot, respectively, was the same.…”
Section: Resultsmentioning
confidence: 99%
“…Nesse caso, os valores genotípicos preditos (ou os dados originais) são expressos como proporção da média geral de cada local e, posteriormente, obtém-se o valor médio dessa proporção através dos locais. A seleção simultânea por produtividade, estabilidade e adaptabilidade, no contexto dos modelos mistos, pode ser realizada pelo método da média harmônica da performance relativa dos valores genéticos (MHPRVG) preditos (Silva et al 2011;Rosado et al 2012).…”
Section: Introductionunclassified
“…Babić et al (2010) report that several years have gone by trying to summarize the effects of the GxE interaction in only one univariate statistic (though it is conceptually multivariate) and they state that recent studies have shown this concept must be abandoned. Silva et al (2011) mentioned that methods that use a multivariate approach, such as the Additive Main Effects and Multiplicative Interaction (AMMI) model (Zobel et al 1988) and Genotype plus Genotype x Environment (GGE) biplot (Yan et al 2000), more properly explain the main effects (genotypes and environments) and their interaction. Another multivariate method, proposed by Murakami and Cruz (2004), is factor analysis of the matrix of the adjusted phenotypic mean values of the genotypes in the environments.…”
Section: Introductionmentioning
confidence: 99%